101 : Eesti Maalikunstnike liit 1977 = Estonian Painters' Association 1977. - Bernstein, Boris; Levin, Mai; Ziterova, Ninel (Tallinn : Estonian Painters' Association Tallinn, 1997)
Allik, Paul ; Allsalu, Vano ; Arrak, Jüri ; Arro, Jaak ; Aru, Inga ; Baciu, Vladimir ; Bormeister, Marju ; Büttner, Owe ; Dzidzaria, Urve Sunny ; Eher, Silva ; Eist, Aksel ; Elken, Jaan ; Eller, Voldemar ; Fuks, Margarethe ; Guli, Nikolai ; Hoffmann, Dolores ; Jaanson, Tiit ; Jaanus, Hillar ; Jänes, Eeva-Aet ; Kaasik, Kristiina ; Kaasik, Peeter ; Kaljo, Kai ; Kari, René ; Kasemaa, Saskia ; Kask, Jüri ; Kelpman, Rein ; Keskküla, Ando ; Kesler, Kaja ; Kilk, Miljard ; Kimm, Ilmar ; Kokamägi, Epp-Maria ; Koll, Maire ; Kormasov, Nikolai ; Kormasov, Orest ; Korstnik, Ene ; Kristerson, Aimar (Kreg A-Kristring) ; Kruusamäe, Ilmar ; Kruusing, Agur ; Kurismaa, Kaarel ; Kurismaa, Mari ; Kurvitz, Raoul ; Leis, Malle ; Lill, Ado ; Lobanov, Andrei ; Luik, Airi ; Maran, Olav ; Matsu, Krista ; Minhailov, Konstantin ; Mosolainen, Lilian ; Mudist, Peeter ; Muru, Urmas ; Muuga, Leili ; Nagel, Lemming ; Ohakas, Valdur-Olev ; Okas, Evald ; Ole, Kaido ; Pallo-Vaik, Tiiu ; Palm, Jüri ; Paris, Mall ; Paris, Väino ; Parmasto, Anne ; Pedanik, Urmas ; Pere, Peeter ; Pihelga, Agu ; Polli, Heitti ; Polli, Kalio ; Prostin, Sirje ; Prääts, Rait ; Poldroos, Enn ; Pääsuke, Tiit ; Raamat, Rein ; Randjärv, Saima ; Rattus, Kersti ; Rohusaar-Meres, Piret ; Roode, Esther ; Roosvalt, Mari ; Roosvalt, Uno ; Runge, Sirje ; Rouk, Andrus ; Sarapuu, Lembit ; Sein, Valev ; Sepping, Peeter ; Sillak, Lauri (Laurentsius) ; Sinjukajev, Viktor ; Strahhov, Anatoli ; Subbi, Olev ; Tammetalu, Tiina ; Teder, Ülo ; Tegova, Enn ; Terri, Olga ; Tolts, Andres ; Toomik, Jaan ; Tonissoo, Toomas (Tommy) ; Uiga, Sigrid ; Vahersalu, Helle-Reet ; Vene, Einar ; Viidalepp, Ants ; Vinogradov, Valeri ; Vint, Aili ; Vint, Toomas ; Väli, Voldemar
Bibliog. p. 220-224
Engels
Ests
boek
Keywords: Estland; Estonia